In Search Of ‘suitable Positions’ In The Asia-pacific: Negotiating The Us-china Relationship And Regional Securityin Search Of ‘suitable Positions’ In The Asia-pacific: Negotiating The Us-china Relationship And Regional Security - Goh, Evelyn (2016)
This paper argues that the crucial determinant of Asia-Pacific security is whether the US and China can negotiate their relationship and their relative positions and roles in such a way as to produce sustainable regional stability. It examines three alternative models to assess some of the possible processes and outcomes in negotiating Sino-American coexistence. (I) Power transition, in which there is a significant structural shift in the regional system as a rising China challenges US dominance, with a range of possible outcomes; (II) The maintenance of the status quo of US strategic dominance over the region, which China does not challenge concentrating instead on internal consolidation and on developing its economic power; and (III) Negotiated change, by which the two powers coordinate to manage a more fundamental structural transformation, either through forming a concert (duet) of power, or by moving towards a regional security community. The paper suggests that Model II is likely for the short- to medium-term; Model III for the medium term; and Model I for the long term.